Community-Based Sustainable Development Education in the Semangat Karya Village during the Covid-19 Pandemic - Dienny Redha Rahmani (Borneo Community Development, 2022)
The decline in the economy in several countries including Indonesia is the biggest impact in the midst of the current Covid-19 pandemic. the community also feels the same in the field of education. issue of concern, of course, is the cleanliness of the environment. Environmental cleanliness supports two aspects at once. Namely, environmental quality and preventing the spread of the COVID-19 virus. There are three points of sustainable development that are introduced alternative activities to the community. Namely, an independent economy through training in making sasirangan, improving education through the movement to assist children's education, and habituation of community service for children. The results of the activity show the public's interest in community-based sustainable development education during the COVID-19 pandemic. The public finally understands that activities based on sustainable development can encourage economic independence, improve the quality of education, be prepared for the COVID-19 pandemic, and of course maintain the quality of the environment by itself.